Experimental investigation of a distributed propulsion system - Mehta, Ronak Chittesh (Nanyang Technological University, 2022)
Numerous studies have investigated the concept of distributed propulsion system and its various effects on the performance of aircrafts due to its growing popularity and advantages. Multiple factors and parameters were studied. However, there lies a gap that has limited studies that consider the relative angle between the propeller mounting and the airfoil. This project aims to investigate that research gap experimentally for a NACA 2412 airfoil with 4 mounted, adjustable propellers. Three deflection angles with respect to the airfoil, and four throttle speed settings tested. It was found that with the increase in throttle speed, both lift and stall angles were increased. As for drag, the slope of the curve became steeper and more exponential as throttle was increased. Aerodynamic efficiency also increased with throttle, but this trend was only consistent around the region of optimal efficiency. These trends were synonymous for both 10° and 20° deflections of propellers as well. In addition, with an increase in deflection angle for propellers within the same throttle speed, lift and stall angle were seen to increase as well with the most increase of stall angle occurring with deflections at 35% throttle speed. Aerodynamic efficiency saw a greater extent of improvement with increasing deflection. Another configuration was also tested, with an opposite rotation direction of the propellers, with similar parameters and showed an overall better performance than the prior configuration through higher lift and lower drag at all parameters resulting in a higher aerodynamic efficiency.